Microbial cross contamination in household laundering and microbial ecology of household washing machines - Whitehead, Kelly; Eppinger, Jake; Srinivasan, Vanita; Ugalde, Juan A. (Frontiers in Microbiology, 2025)
Household washing machines host diverse microbial communities that may include opportunistic pathogens, potentially impacting laundry hygiene and human health. However, our understanding of these communities and their transfer abilities remains limited. We examined microbial communities from 10 household washing machines (five front-load and five top-load) using surface swabs from specific hotspots and sterile sentinel washcloths. Samples were analyzed using culture-based methods and 16S rRNA/ITS metabarcoding. We tested microbial transfer during washing cycles with and without clothing and evaluated the effects of machine drying on this transfer. Front-load machines had significantly higher microbial loads than top-load machines (average bacterial counts: 6.50 ± 2.46 Log10/swab vs. 3.79 ± 1.73 Log10/swab). The microbial community composition was mainly shaped by the machine user rather than the machine type or sampling location. The dominant bacterial genera included Pseudomonas, Micrococcus, and Sphingomonas, while Aspergillus, Cladosporium, and Penicillium dominated the fungal communities. Opportunistic microorganisms were identified, but no highly pathogenic species (pathogenicity score 3) were found. Machine drying did not significantly decrease microbial loads, whereas the presence of soiled clothing impacted community composition. Household washing machines host user-specific microbial communities, including potential opportunistic pathogens. Current laundry practices may be inadequate for the complete elimination of pathogens, especially in immunocompromised individuals. These results support the need for additional household laundry sanitization strategies.